Canalicular Curettage to the Rescue: a report of three cases - Sahu, Sabin; Kafle, Prerna Arjyal; Hamal, Diwa; Gupta, Adit; Ram, Dipesh Kumar; Singh, Sanjay Kumar (Nepalese Journal of Ophthalmology, 2020)
Introduction: Canalicular curettage is a surgical procedure used to remove canalicular contents and debris from canaliculi. It is usually indicated for chronic, persistent or recalcitrant canalicular diseases with no resolution of symptoms after conservative management. We describe 3 different cases of persistent canalicular diseases which needed canalicular curettage to rescue from the conditions leading to successful outcomes. Cases and observations: • Case 1: A 45-year-old male presented with recurrent punctal granuloma 3 months after DCR surgery. Canalicular exploration and curettage with one-snip punctoplasty following excision of the mass revealed a segment of remnant silicone stent. There was no recurrence of mass in subsequent follow up visits. • Case 2: A 35-year-old female presented with recurrent canaliculitis for last 6 months. Canalicular curettage revealed multiple small calcified masses of varying size and shape. The patient had good postoperative recovery and showed no recurrence of symptoms. • Case 3: A 32-year-old female presented with gradually increasing pedunculated mass arising out of punctum for last one month. Excision of mass with canalicular curettage was done. Biopsy proved it to be squamous papilloma of the canaliculi. There was no recurrence of mass. Conclusion: Canalicular curettage is a simple, safe and effective surgical intervention to rescue from the recalcitrant canalicular conditions like canaliculitits, retained foreign bodies, canalicular neoplasms leading to successful outcomes.